2019
DOI: 10.1289/ehp5482
|View full text |Cite
|
Sign up to set email alerts
|

Perfluoroalkyl Substances and Maternal Thyroid Hormones in Early Pregnancy; Findings in the Danish National Birth Cohort

Abstract: Background:Maternal thyroid hormones are essential for fetal brain development in early gestation. Perfluoroalkyl substances (PFASs)—widespread and persistent pollutants—have been suggested to interfere with maternal thyroid hormones in the second or third trimesters, but evidence for an association in the early pregnancy period is sparse.Objectives:Our goal was to evaluate the gestational-week specific associations of maternal thyroid-stimulating hormone (TSH) and free thyroxine (fT4) levels with plasma conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 60 publications
(104 reference statements)
2
24
0
Order By: Relevance
“…Two studies found significantly decreased maternal TSH levels with increasing PFOS, PFNA, PFDA, PFUnA and PFDoA concentrations [38,46], which might indicate a hyperthyroid maternal state. None of the ten studies investigating the association between PFOA concentration and maternal TSH found any significant results [38][39][40][41][42][43][44][45][46][47]. However, it should be noted that all these PFAAs are often highly intercorrelated.…”
Section: Tshmentioning
confidence: 95%
See 2 more Smart Citations
“…Two studies found significantly decreased maternal TSH levels with increasing PFOS, PFNA, PFDA, PFUnA and PFDoA concentrations [38,46], which might indicate a hyperthyroid maternal state. None of the ten studies investigating the association between PFOA concentration and maternal TSH found any significant results [38][39][40][41][42][43][44][45][46][47]. However, it should be noted that all these PFAAs are often highly intercorrelated.…”
Section: Tshmentioning
confidence: 95%
“…We found 15 original publications that fulfilled the inclusion criteria [38][39][40][41][42][43][44][45][46][47][48][49][50][51][52] (Table 2). Study populations varied from 118 to 1366 participants [40,51], conducted in Asia (n = 6), Europe (n = 6) and Northern America (n = 3). Study designs were cross sectional and/or cohort studies.…”
Section: Study Populationsmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study that investigated maternal infections or antibiotic use and CP risk in the offspring also reported the strongest associations in the first trimester [66]. Our own studies in the Danish cohort indicated that endocrine-disrupting compounds might interfere with the dynamics of maternal thyroid hormones in early gestation [67], and maternal thyroid function abnormalities were associated with adverse motor function in young children [68]. The early gestational period might be a critical time window for environmental exposures affecting CP risk.…”
Section: Discussionmentioning
confidence: 54%
“…The persistent PFAS have been shown to be highly correlated using repeated blood samples in the first and the second trimesters collected in the DNBC (Fei et al 2007). However, effect measure modification by gestational week of sampling is also possible and has recently been suggested for the thyroid hormone changes in early pregnancy (Inoue et al 2019). Our stratified analyses suggested a stronger effect estimate for samples collected after gestational week 8, but the stratified analyses were imprecise and need to be reevaluated in future research.…”
Section: Discussionmentioning
confidence: 76%